Translation of Enterprise Architecture Concept to Facilitate Digital Transformation Initiatives in Vietnam : Processes, Mechanisms and Impacts - Dang, Duong; Bui, Quang “Neo” (Association for Information Systems, 2023)
Governments around the world have increasingly adopted digital transformation (DT) initiatives to increase their strategic competitiveness in the global market. To support successful DT, governments have to introduce new governance logics and revise IT strategies to facilitate DT initiatives. In this study, we report a case study of how Enterprise Architecture (EA) concepts were introduced and translated into practices in Vietnamese government agencies over a span of 15 years. This translation process has enabled EA concepts to facilitate various DT initiatives such as e-government, digitalization, to name a few. Our findings suggest two mechanisms in the translation process: a theorization mechanism to generalize local practices into field-level abstract concepts, making them easier to spread, while a contextualization mechanism unpacks these concepts into practical, adaptable approaches, aligning EA with adopters' priorities and increasing its chances of dissemination. Furthermore, our findings illustrate how translation happened when the initial concepts are ambiguous and not-well-understood by adopters. In this situation, there is a need for widespread experiments and sense-making among pioneers before field- and organizational-level translation can occur.
Keywords: Translation; digital transformation; theorization; contextualization; enterprise architecture; fi=Tietojärjestelmätiede|en=Information Systems|